Assessment of antiplaque effectiveness of chlorhexidine‐soaked gauze compared to chlorhexidine mouth rinse: Randomized clinical trial. Issue 3 (17th February 2018) - Sparabombe, Scilla; Roncati, Marisa; Monterubbianesi, Riccardo; Catellani, Alberto; Manzoli, Lamberto; Bambini, Fabrizio; Procaccini, Maurizio; Putignano, Angelo; Orsini, Giovanna
Abstract: Aim: The aim of the present study was to compare the efficacy of a disposable gauze soaked with chlorhexidine and rolled up on the finger vs chlorhexidine mouth rinse (CM) to maintain oral hygiene. Methods: In this single‐blind, randomized trial, both groups were instructed to brush their teeth and use the 0.12% chlorhexidine intervention twice per day (experimental group: toothbrushing + chlorhexidine‐soaked gauze; control group: toothbrushing + mouth rinse). The main outcome was the change in full mouth plaque index scores from baseline to 2 weeks. Secondary outcomes were the patient's appreciation (visual analog scale) and the bleeding index. Results: The final sample consisted of 60 young patients: 31 in the experimental group and 29 in the control group. After 2 weeks, both interventions were effective in reducing plaque index. The percentage of score reduction was 33% in the experimental group and 30% for the controls, with no significant difference between groups. Both interventions reduced the bleeding index, but this reduction was significant only in the experimental group ( P < .001). Conclusions: There is no difference between chlorhexidine‐soaked gauze and CM regarding plaque control. In addition, gauze soaked with chlorhexidine was significantly more effective in reducing the bleeding index score and was appreciated by the patients.